2013
DOI: 10.1007/s00251-013-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

The repertoire of MHC class I genes in the common marmoset: evidence for functional plasticity

Abstract: In humans, the classical antigen presentation function of major histocompatibility complex (MHC) class I molecules is controlled by the human leukocyte antigen HLA -A, HLA-B and HLA-C loci. A similar observation has been made for great apes and Old World monkey species. In contrast, a New World monkey species such as the cotton-top tamarin (Saguinus oedipus) appears to employ the G locus for its classical antigen presentation function. At present, little is known about the classical MHC class I repertoire of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
4
23
2
Order By: Relevance
“…The remaining 562-kb segment (321 kb in contig 1, 141 kb in contig 2, and 100 kb in contig 3), including the duplicated Caja-G/F genes, is represented only by several mini contigs in the WUGSC 3.2 sequence (Table II), which is most likely due to the current quality (draft assembly and not finished sequence) of the common marmoset draft genome sequence. Genomic diversities in the Caja-G loci were suggested to be generated considerably after duplication based on the population study of the Caja-G genes (13). This finding supports that genomic structures of the Caja-G/F segment are different among the Caja-G/F haplotypes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The remaining 562-kb segment (321 kb in contig 1, 141 kb in contig 2, and 100 kb in contig 3), including the duplicated Caja-G/F genes, is represented only by several mini contigs in the WUGSC 3.2 sequence (Table II), which is most likely due to the current quality (draft assembly and not finished sequence) of the common marmoset draft genome sequence. Genomic diversities in the Caja-G loci were suggested to be generated considerably after duplication based on the population study of the Caja-G genes (13). This finding supports that genomic structures of the Caja-G/F segment are different among the Caja-G/F haplotypes.…”
Section: Discussionsupporting
confidence: 77%
“…From the MHC-B/C segment, which has been under permanent selective pressure in the evolution of primates, a genomic sequence of 1179 kb was determined that includes nine duplicated Caja-B genes (12). In contrast, although four to seven Caja-G-like alleles were detected in each common marmoset from a recent population study (13), the genomic structure of the Caja-G/F segment between GABBR1 and ZNRD1 is still not solved, and 54 alleles of Caja-G and Caja-E are currently listed in the Immuno Polymorphism Database (IPD)-MHC database (14).…”
mentioning
confidence: 99%
“…In our study, 480 sequences of 21 common marmosets were analysed and classified as members of the Caja-G family. Comparison with already confirmed Caja-G sequences [26][27][28] resulted in 34 different alleles in our investigated group of animals. Four of the detected alleles have been published before 26,27 and a total of 30 new alleles, concerning the sequence of exon 1-4, were uploaded to the NCBI database and are presented in Table 1 with GenBank accession numbers, official IPD-MHC nomenclature and number of animals that shared the correspondent alleles.…”
Section: Identification Of Caja-g Allelessupporting
confidence: 65%
“…Comparison with already confirmed Caja-G sequences [26][27][28] resulted in 34 different alleles in our investigated group of animals. Four of the detected alleles have been published before 26,27 and a total of 30 new alleles, concerning the sequence of exon 1-4, were uploaded to the NCBI database and are presented in Table 1 with GenBank accession numbers, official IPD-MHC nomenclature and number of animals that shared the correspondent alleles. Of 34 MHC class I sequences most alleles were found in one (15) or two (10) marmosets, whereas other alleles like Caja-G*08:23 occurred in 11 different marmosets, that originated from different families (compare Fig.…”
Section: Identification Of Caja-g Allelessupporting
confidence: 65%
“…Shiina et al determined the gene structure of Caja-G. The Caja-G gene cluster contains 14 loci, at least 5 of which express functional gene products (25); plural alleles have been found in these loci (26)(27)(28)(29). The variation and the binding of peptide suggested that it is more similar to classical HLA in humans, but the real function of Caja-G is yet to be clarified.…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%